Penerapan Model Pembelajaran Problem Solving untuk Meningkatkan Hasil Belajar Pendidkan Agama Islam - Hidayah, Nurul; Harahap, Hotni Sari; Harahap, Azrai; Haidir, Haidir (Hikmah, 2023)
The problem encountered at Al Maksum Percut Sei Tuan High School is that classroom learning tends to use a direct approach that focuses on the teacher (teacher center) while students are passive when learning activities take place. This passivity makes students feel bored and has an impact on low student learning outcomes. In addition, the inappropriate selection of methods, models and strategies is also a factor in not optimizing the learning outcomes obtained by students. This study aims to determine student learning outcomes before and after the application of the problem solving learning model. This class action research was conducted in two cycles, where each cycle consisted of four stages, namely: planning, implementation, observation and reflection. The subjects in this study were students of class XI SMA Al maksum precut Sei Tuan which amounted to 25 students. The learning outcomes obtained by students in cycle I obtained 13 students who were complete in learning, and 12 students who were not complete with a percentage of completeness of only 52% and an average score of 65.32. And in cycle II, 21 students were obtained who were complete and 4 people who were not complete, with the percentage of completeness reaching 84% and the average score was 72.08.Keywords: Education innovation, Human resources, Islamic education.